2013
DOI: 10.1179/1743676113y.0000000131
|View full text |Cite
|
Sign up to set email alerts
|

Reusing coffee waste in manufacture of ceramics for construction

Abstract: This paper aims at studying the influence of different clay/coffee waste mixtures in structural ceramics by incorporating different amounts of spent coffee grounds as an additive. Clay paste with 5, 10, 15 and 20 wt-% of coffee waste was used to mould clay bodies, which were then fired at the temperatures of 900, 1000 and 1100uC. Morphological aspects were evaluated through SEM images, while several laboratory tests provide the physical and mechanical properties. Incorporation of coffee waste increases the wat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(27 citation statements)
references
References 37 publications
1
26
0
Order By: Relevance
“…Furthermore, coffee parchment and SCG have been used as fillers of polyurethane composites 123 , and SCG has been proposed as an additive in the production of ceramic bricks, showing acceptable physical and mechanical performance and low thermal conductivity. 124 From an agricultural point of view, the possibility of reutilizing spent coffee grounds as an easy and economically feasible soil amendment, represents an exciting opportunity to obtain products of high nutritional value. 125 For instance, low amounts of composted-SCG (up to 15% v/v) produced a relevant increase in essential macro-elements in lettuce, enhancing its quality features.…”
Section: Other Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, coffee parchment and SCG have been used as fillers of polyurethane composites 123 , and SCG has been proposed as an additive in the production of ceramic bricks, showing acceptable physical and mechanical performance and low thermal conductivity. 124 From an agricultural point of view, the possibility of reutilizing spent coffee grounds as an easy and economically feasible soil amendment, represents an exciting opportunity to obtain products of high nutritional value. 125 For instance, low amounts of composted-SCG (up to 15% v/v) produced a relevant increase in essential macro-elements in lettuce, enhancing its quality features.…”
Section: Other Applicationsmentioning
confidence: 99%
“…Hirata et al 111 , Franca et al 112 , Nakamura et al 113 , Namane et al 114 Animal feed Claude 121 , Givens and Barber 122 Ceramic manufacturing Sena da Fonseca et al 124 Composite materials Funabashi et al 123 Superscript numbers correspond to the cited literature…”
Section: Biosorbentsmentioning
confidence: 99%
“…The coffee waste stream becomes a relevant problem not only after consumption but also during the wet processing of coffee beans when 1 ton of fresh berries results in only about 400 kg of wet waste pulp. Several solutions have been proposed to solve the problem of waste coffee biochar, such as the production of biogas [4] and flavours [5], use as filler in ceramics [6] or as absorbent for the removal of basic dyes from aqueous solutions [7]. Coffee wastes have been also used as feedstock for pyrolytic conversion producing hydrogen-rich gas [8] and fuel-quality biochar [9].…”
Section: Introductionmentioning
confidence: 99%
“…There have been various attempts in using WCG but most of these methods generate byproducts that should be discarded in landfills or eventually incinerated [3e8]. For example, Sena da Fonseca et al [3] found that WCG can be added to clay ceramics to enhance the mechanical strength due to increased water absorption and porosity. Several research groups [4e8] investigated the adsorption properties of polyhydroxy polyphenol functional groups in WCG and WCGderived char on heavy metals.…”
Section: Introductionmentioning
confidence: 99%